Robert Griffiths Hodgins and tragicomedy - Lindeque, Nicole (My University, 2011)
This dissertation offers the dramatic genre of tragicomedy as a critical entry point to the interpretation of Robert Hodgins' oeuvre. It examines the possible formal corresponding properties between tragicomedy, as outlined by Verna Foster, and selected paintings from Hodgins' oeuvre. These mechanisms involve the juxtaposition of conflicting impressions, such as those created by instances of the grotesque, the employment of multiple perspectives and the play-within-the-play. The paintings Madhouse with a View of Tyburn, Three Characters in Search of a Painter– and I know some smart-ass critic will say: 'Well, they didn't find him, did they?' and A Conservative Still Life feature in this discussion. It addresses tragicomedy and Hodgins' dualist visions and their potential to be interpreted politically as oblique comments on homogenised culture. It discusses tragicomedy as an ambivalent and abrasive theatrical form and suggests that the deliberate artifice in both Hodgins and tragicomedy can be approached as a mental projection. The plot features of Renaissance and late modern tragicomedy are compared to Hodgins' employment of anonymous figures and the figures' relation to their backgrounds. The notion of late modern tragicomedy as indicative of the death of tragedy and the tragic hero is introduced. The proliferation of everyday people as central characters in late modern tragicomedy is addressed and the relevance of Hodgins' use of stereotypes and caricature considered. The dissertation examines the political climate that informed the presentation of power of pertinent creative practitioners. A Beast Slouches is discussed as a manifestation of absurd power with reference to Yeats, Shakespeare and Jarry. It investigates Hodgins' appropriation of Jarry's Ubu as displayed in the lithograph series, Ubu Centenaire: Histoire d'un Farceur Criminel and draws a comparison with Ionesco's Macbett. It introduces the view of tragicomedy as the employment of a comic foundation with which to approach the tragic in a post Second World War paradigm and reasons that Hodgins, likewise, formally applies a comic caricature-like visual language to approach complex or tragic themes. The works on my exhibition, Masters: A Tragicomedy in Two acts of February 2011 is discussed in relation to this body of research.
MA (Fine Art), School of Arts, Faculty of Humanities, University of the Witwatersrand, 2011
Keywords: tragicomedy; Robert Hodgins; paintings; visual interpretation